1966
DOI: 10.1017/s0068245400019031
|View full text |Cite
|
Sign up to set email alerts
|

A Group of Late Helladic IIIB 1 Pottery from Mycenae

Abstract: The L.H. IIIB deposits from Mycenae fall into two distinguishable groups. The earlier, called L.H. IIIB 1, is represented by the pottery from the destruction level in the houses east of the modern road and south of the tomb of Clytemnestra. The destruction to which we owe these deposits appears to have occurred late in the L.H. IIIB 1 phase, and probably also affected the houses on the Atreus ridge. The later group, classified as L.H. IIIB 2, has been found in buildings within the Citadel and also in isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(60 citation statements)
references
References 0 publications
1
58
0
1
Order By: Relevance
“…The height of curved wall α is only about 0.20 m (Hood 1953a, 24; X048, 110; Taylour 1955, 209; X1076, 61). Curved wall α, like the rest of the foundation, lies partly on earth (PCC III) and partly on bedrock (PCC IV) and showed that the Great Poros Wall was not set in a foundation trench (Hood 1953a, 23–4; X048, 113; French 1966, 217 n. 10).…”
Section: The Great Poros Wallmentioning
confidence: 99%
See 3 more Smart Citations
“…The height of curved wall α is only about 0.20 m (Hood 1953a, 24; X048, 110; Taylour 1955, 209; X1076, 61). Curved wall α, like the rest of the foundation, lies partly on earth (PCC III) and partly on bedrock (PCC IV) and showed that the Great Poros Wall was not set in a foundation trench (Hood 1953a, 23–4; X048, 113; French 1966, 217 n. 10).…”
Section: The Great Poros Wallmentioning
confidence: 99%
“…This is because the relationship between this layer and the retaining wall gives us the stratigraphic sequence, which enables us to use the deposit of pottery found in trenches III and IV of the Prehistoric Cemetery Central to date the tomb. Fortunately, the pottery from PCC III and IV has been published (see French 1966).…”
Section: The Relevant Trenchesmentioning
confidence: 99%
See 2 more Smart Citations
“…A general trend for geometric and symmetrical organization of the motifs can be seen in their arrangement between triglyphs and the restriction of the free composition on the surface of the vase. The large percentage of kylikes and the absence of type A deep bowls suggest an LH IIIB1 date (Mountjoy 1986, 121;French 1966;1967). 19…”
Section: History Of Bronze Age Research On Naxosmentioning
confidence: 99%